Panmen Pound Panvesco - Persad, Siewdath (The Independent)
Pan Trinbago Investment Corporation (Panvesco), the investment arm of the national steelband administration, was subjected to heavy criticisms during Pan Trinbago’s general meeting.
Keywords: Pan Trinbago (Organization); Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel bands (Music) -- Finance -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago